Tuberculosis in children: The importance of screening - Silva, Sílvia Ferreira (2013)
Introduction: Tuberculosis (TB) is a major problem in public health. Every year there are about 9 million new cases and around 2 million deaths worldwide. Control of TB in children is often been neglected, as children are considered less contagious than adults. Case report: We report the case of an 2 year-old girl diagnosed with pulmonary tuberculosis following screening of contacts with a great-uncle who was diagnosed with pulmonary tuberculosis in the contagious phase. Comment: In children, screening of TB is important because children can act as reservoirs of the disease, with subsequent morbidity and mortality from TB in childhood.